1998
DOI: 10.1152/ajpregu.1998.274.5.r1260
|View full text |Cite
|
Sign up to set email alerts
|

Changes in extracellular serotonin in rat hypothalamus affect thermoregulatory function

Abstract: Experiments were carried out to determine the effects of altering the serotonin (5-HT) levels in the hypothalamus on thermoregulatory function in unanesthetized restrained rats. Local perfusion of the hypothalamus with dialysis solution containing 5-hydroxytryptophan (a 5-HT precursor), fluoxetine (a 5-HT reuptake inhibitor), or high potassium significantly increased both colonic temperature (Tco) and the extracellular concentrations of 5-HT in the hypothalamus. Reciprocally, both extracellular concentration o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
83
0
1

Year Published

2003
2003
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(90 citation statements)
references
References 41 publications
6
83
0
1
Order By: Relevance
“…Hypothermia was mediated by many types of receptors including serotonergic 5-HT 1A (Hillegaart, 1991;Millan et al, 1993;Lin et al, 1998), 5-HT 7 (Guscott et al, 2003;Faure et al, 2006), dopaminergic D 2 (Oerther, 2000) and adrenergic α 2 receptors (Feleder et al, 2004). It appears that both 5-HT 1A and 5-HT 7 receptors exerted a small tonic inhibition on T cor , consistent with the role of those binding sites in thermoregulation (Lin et al, 1998). Using the selective 5-HT 7 receptor antagonist SB-639970 we ruled out a possible involvement of 5-HT 7 receptors in hypothermia under our experimental condition.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hypothermia was mediated by many types of receptors including serotonergic 5-HT 1A (Hillegaart, 1991;Millan et al, 1993;Lin et al, 1998), 5-HT 7 (Guscott et al, 2003;Faure et al, 2006), dopaminergic D 2 (Oerther, 2000) and adrenergic α 2 receptors (Feleder et al, 2004). It appears that both 5-HT 1A and 5-HT 7 receptors exerted a small tonic inhibition on T cor , consistent with the role of those binding sites in thermoregulation (Lin et al, 1998). Using the selective 5-HT 7 receptor antagonist SB-639970 we ruled out a possible involvement of 5-HT 7 receptors in hypothermia under our experimental condition.…”
Section: Discussionmentioning
confidence: 99%
“…Thus behavioral signs and symptoms can be mild, moderate or severe (Boyer and Shannon, 2005). Changes in body-core temperature (claudqcT cor ), attributable to 5-HT-mediated thermoregulation in the central nervous system (Lin et al, 1998), are a most obvious indication for the toxidrome (Isbister and Buckley, 2005). Several studies conducted in animals have revealed both hyperthermia and hypothermia in the toxidrome (Abdel-Fattah et al, 1995, 1997Nisijima et al, 2001Nisijima et al, , 2003.…”
Section: Introductionmentioning
confidence: 99%
“…Fluoxetine can induce hyperthermia in rats (Lin et al, 1998). The activity of PLA 2 as well that of other enzymes might be expected to increase with an increase in temperature .…”
Section: Saline Control Fluoxetinementioning
confidence: 98%
“…It has been described that local perfusion of the hypothalamus with 5-hydroxytryptophan (a 5-HT precursor) or fluoxetine (a 5-HT reuptake inhibitor) increases body temperature by increasing extracellular concentrations of 5-HT, which activate central 5-HT 2A receptors [20,21], although activation of these receptors in the peripheral system leads to hypothermia [22]. Additionally, an activation of 5-HT 1A receptors in the hypothalamus leads to hypothermia [23].…”
Section: Discussionmentioning
confidence: 99%